Systemic immune response at gastroesophageal reflux disease - Yu. V. Yevsyutina; A. S. Trukhmanov; V. T. Ivashkin; S. V. Lyamina; I. Yu. Malyshev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To characterize the systemic immune response at patients various forms of gastroesophageal reflux disease (GERD).Material and methods. Overall 45 patients with GERD and 10 healthy volunteers were included in prospective study. All patients underwent following investigation: taking complaints and past history, detection of GERD risk factors; esophagogastroduodenoscopy and 24-hour рН-impedance recording. Levels of 7 cytokines were determined by flow cytofluorometry: two antiinflammatory: IL-4 and IL-10, three proinflammatory: IL-8, IFN-γ and TNF-α and two cytokines which can demonstrate both anti-inflammatory and proinflammatory activity in relation to conditions (bivalent) — IL-2 and IL-6.Results. Patients with erosive and/or ulcerative esophagitis in comparison to patients with non-erosive reflux disease (NERD), Barret's esophagus and healthy patients had increased expression of proinflammatory cytokines. In patients with Barret's esophagus in comparison to others GERD patients and healthy volunteers hyperproduction of anti-inflammatory cytokines was revealed. TNF-α and IL-8 levels correlated to total number of acidic refluxes and exposition of acidic bolus, while IL-4 and IL-10 level — with total number of weakly alkaline refluxes and exposition of weakly alkaline bolus. High level of IL-8 was associated with increased frequency of relapses of erosive esophagitis within 2 years, despite of carried out therapy.Conclusions. Relation of cytokine levels to the form of GERD was revealed. At erosive and/or ulcerative esophagitis in comparison to NERD and Barret's esophagus production of proinflammatory cytokines IL-8, the IFN-γ and TNF-α prevails, that indicates development of Th1-mediated immune response. At Barret's esophagus expression of anti-inflammatory cytokines IL-4 and IL-10 is increased, that indicates on development of Th2-immune response.